CONSUMER TRENDS IN BAKERY MARKET: UNDERSTANDING OF CONSUMER PERSPECTIVES AND PREFERENCES FOR FUNCTIONAL BAKERY PRODUCTS IN SLOVAKIA - Predanócyová, Kristína; Šedík, Peter; Pocol, Cristina Bianca (Economics of Agriculture, 2026)
The aim of the paper is to identify key consumer attitudestowards functional bakery products and explore factors affectingconsumer behavior. The study is based on questionnaire surveyconducted on a sample of 775 functional bakery productsconsumers in Slovakia. The results showed that consumersprefer grain and whole wheat bread, while sweet pastries withlow-calorie sweeteners are the least consumed. Furthermore,key factors influencing purchase are freshness, quality, taste,and health benefits. The results indicated that consumers arechoosing products based on increased whole grain content,fiber, and minerals and key reasons for consumption arereducing obesity risk and supporting digestive health. Thestudy also pointed out consumer awareness and interest inhealthy eating as key drivers for future market development.Findings provide valuable information to food companies inthe new bakery products development and marketing, as wellas to policy makers in supporting the public health.